APPLICATIONS AND EFFECTS OF FLEXIBLE WORKING AS AN ALTERNATIVE TYPE OF WORK - Şenol YAPRAK (Fırat University, 2019)
Although flexible working does not have a very old background, it has a history of half a century. Flexible working doesn’t have a very long history in Turkish Working Life and it is quite new in labour law. This type of working results from a need and this need is sometimes revealed by an employer or sometimes by an employee. Flexible working is a form of working that increases employment for a group of people and provides an oppurtunity for people who would be out of working life on the condition of strick rules. For some others, flexible working means a work that prevents unionism and acts as a mean of dissepearing the benefit obtained before. In spite of criticism, working life progresses in the direction of flexible working application more. In spite of criticism, working life progresses in the direction of flexible working application more. There are many factors that have influenced flexible working in gaining importance recently. Working methods have also become different as a result of changes in the working life especially depending on rapidly developing technology, new types of employment and working methods have revealed. Furthermore, people demand to have more free time and try to balance their working life and family life more. Employees who did not expect such things because of rigid rules and working methods in the past can understand that it is possible now. They also believe that flexible applications can be more flexible. In our current global World, working life is changing, instead of a an arrangement dominated by employers’ demands, a system in which demands and expectations of employees are important is developing. One of these expectations is that more flexible working time and types perform in order to balance between work life and family life of employees leaving rigid and standard working types. It can be said that flexible working application revealed with the aim of meeting this need. In this study, it was tried to reveal what these applications were and how organizations and employees were affected by the applications.